The Moderating Effect of Service Quality on the Relationship between Income and Tax Compliance - Arifiyanto, Nur Muhammad; Bunyamin, Bunyamin; Wiyarni, Wiyarni (Technium Social Sciences Journal, 2024)
This research aims to test 1) the effect of income on tax compliance, 2) the effect of service quality on tax compliance, 3) the effect of income on tax compliance with service quality as a moderating variable. The approach used in this research is quantitative. The sample in this study was 140 taxpayers who paid motor vehicle tax at the Situbondo Regency SAMSAT Office. The data collection technique uses a questionnaire with a Likert scale and data analysis uses multiple linear regression analysis using SPSS 25.0 for Windows. Research results: show that 1) Income has a significant effect on tax compliance, 2) Service quality has a significant effect on tax compliance, and 3) Service quality moderates the effect of income on tax compliance.